In “J” Laparotomy. An Alternative Pathway for High Abdominal Surgery (International Journal of Medical and Surgical Sciences, 2014)
Pathways for high abdominal surgery (HAS) are vertical, oblique and transverse laparotomies. A variety of these is known as “in J laparotomy” (JL). The aim of this study is to analyze the results obtained with JL in HAS, in terms of local postoperative complications (LPC) respect of vertical laparotomies (VL). Historical cohort study. The sample consisted of patients operated for HAS consecutively between 1996 and 2012 (17 years), at the Hospital Clínico de la Universidad Mayor. The outcome variable was development of LPC. Other variables of interest were diagnosed at admission, surgery performed, hospital stay, surgical time and type of wound. The cohort of patients undergoing JL was compared with other patients with VL. The patients had a minimum follow-up of 12 months. Descriptive and analytical statistics (t-test, Chi2 and exact of Fisher) were used. LPC incidence was calculated in both groups. In addition, RR, RAR and NNT were also calculated. The study population was 220 patients, 120 (54.5%) operated with JL and 100 (45.5%) with VL; with a mean age of 45.5 years; 130 (59.1%) women. Diagnoses at intake, type of surgical wound, surgical techniques, surgical time and hospital stay were similar in the study groups. We found no significant differences between groups in the comparative study and incidence of evisceration (p=0.8012) and hernia (p=0.7895). However, significant differences were observed in favor of JL regarding seroma (p=0.0312) and wound infection (p=0.013). In conclusion, JL is safe and comparable with respect to VL in terms of LPC in patients who underwent HAS.